Personality in Adults Who Were Born Very Preterm. - Christin L Hertz; René Mathiasen; Bo M Hansen; Erik L Mortensen; Gorm Greisen (PLoS ONE, 2013)
AIM To investigate the personality in very preterm individuals (VPT; gestational age, GA, <32 weeks) at adult age in two cohorts born in 1974-76 and 1980-82, respectively, and to illuminate the effect of increased survival rates and the clinical implications of deviations in personality. METHOD Demographic data were extracted for all individuals born in Denmark in 1974-76 and 1980-82. From each period one index-group each comprising 150 individuals with the lowest gestational age was selected. Thereafter two control groups born at term were matched by gender, age and residential area. Personality was assessed with the short version of NEO PI-R, and psychiatric diagnoses were obtained from the Danish Psychiatric Central Research Register. RESULTS Of all the individuals born <32 weeks of gestation in 1980-82 67% were alive in 2006 vs. 43% of those born in 1974-76 (p<0.0001). A total of 433 individuals participated in the study, 76% of the VPT groups (n = 227, mean GA = 27.9) and 69% of the control groups (n = 206). There were no significant differences on personality scores between the two VPT groups. Compared to the control groups, the combined VPT groups scored higher on neuroticism (p = 0.005) and agreeableness (p = 0.012), but lower on extraversion (p = 0.002). Psychiatric disorder was strongly associated with higher scores on neuroticism and lower scores on extraversion. INTERPRETATION Improved survival of VPT infants was not associated with increased deviances in the personality as adults. The personality traits in VPT individuals differ moderately from those of term born controls. High scores in neuroticism and low scores in extraversion were associated with increased risk psychiatric disorders. VPT adults also showed signs of positive adaptation in the form of an agreeable and confident attitude towards others. WHAT THIS PAPER ADDS The much improved survival rate in very preterm infants during the early years of active neonatology was not associated with increased risk of personality deviation. There are signs of positive adaptation in the form of increased agreeableness in young adults born very preterm.